THE EFFECTIVENESS OF HOTS-ORIENTED LEARNING ON ACHIEVEMENT OF STUDENT HOTS - La Ode Sirad; Arbain Arbain (JME (Journal of Mathematics Education), 2023)
This research is motivated by the findings regarding the difficulties experienced by students in solving combinatorial problems as an indication of weak High Order Thinking Skills (HOTS) students. The reason is that the lecture process has not facilitated active and interactive student involvement, where the lecture process is dominated by lecturers through the lecture method. Lecturers' formative and summative assessments are mostly because they only access understanding and mastery of the material, are not contextual, and have not facilitated student HOTS achievement. This study aims to improve student HOTS through the application of HOTS-oriented learning. The HOTS-oriented learning components in this study include HOTS-based strategies and models, media, and assessments. The type of research used is a quasi-experimental study with a one-group pretest-posttest design. The sample for this research was 17 students taking discrete mathematics courses for the 2022/2023 Academic Year. The data obtained were analyzed descriptively in the form of mean, standard deviation, and n-gain and inferential analysis using the one-way Multivariate Analysis of Variance (MANOVA) test. The results showed that students' HOTS experienced an increase after applying HOTS-oriented learning in the four aspects of the skills assessed, namely the skills of analyzing, evaluating, and creating; problem-solving skills; creative thinking skills, and critical thinking skills, with an average increase in the medium criteria. Learning that is applied effectively to student HOTS achievement.